Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.

f (x) = 5x – 4, g(x) = x2 + 3x – 8

Evaluate g( f(x) ) for x = 3.

g( f (3)) = g


Sagot :

[tex]g(f(3))=(5\cdot3-4)^2+3(5\cdot3-4)-8=121+3\cdot11-8=146[/tex]
[tex]f\left( x \right) =\quad 5x-4\\ g\left( x \right) =\quad { x }^{ 2 }+3x-8\\ g\left( f\left( x \right) \right) [/tex] 
for x=3

[tex]f(3)=\quad 5\cdot 3-4\\ f(3)=15-4\\ f(3)=11\\ g(f(3))=g(11)\\ g(11)=\quad { 11 }^{ 2 }+3\cdot 11-8\\ g(11)=\quad 121+33-8\\ g(11)=146[/tex]

I hope this was what you asked for.
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.